Clinical efficacy and prediction of response to granulocyte transfusion therapy for patients with neutropenia-related infections - JJ Lee; HC Song; IJ Chung; HS Bom; D Cho; HJ Kim (Haematologica, 2004)
We investigated the efficacy of transfusing granulocytes into 32 patients with severe neutropenia-related infections and the factors that predict response to this therapy. Our findings suggest that granulocyte transfusion therapy is useful for treating neutropenic patients with fungal infections and that 99mTc-HMPAO-granulocyte scintigraphy can be used to predict response to granulocyte transfusion therapy.